The Role of Women in Sustainable Development and Environmental Protection: A Discourse of Ecofeminisme in Indonesia - Oktarina, Tri Nurmega; Yulianti, Anisa (Faculty of Law, Universitas Negeri Semarang, 2022)
Women have been recognized as having an equal role in environmental protection and management. In relation to climate change, for example, internationally, the United Nations Framework Convention on Climate Change recognizes the importance of equal involvement between women and men, in gender-responsive climate policies, through a special agenda that addresses gender issues and climate change, including putting it into the Agreement. Paris. However, until now, the role of women still tends to be neglected, both at the local and national levels. This study aims to analyze and discuss the concept of ecofemenism as a movement for the role of Indonesian women in environmental protection in Indonesia.